Significance of zinc deficiency correction for practical medicine: a review - A. V. Skalny; T. I. Sotnikova; T. V. Korobeynikova; A. A. Tinkov (Сеченовский вестник, 2022)
Zinc deficiency is highly prevalent ranging from 10% to 30–40% of the population in developed and developing countries respectively. Low zinc level has been found to be associated with 0.7% of overall mortality and 1.0% of disability-adjusted life years (DALYs) worldwide. In turn, available research evidence has shown that zinc supplementation in its deficiency can reduce the risk of preterm birth, promote the physical development of children, and have certain protective effect against the components of the metabolic syndrome. A positive effect of zinc supplementation on recovery from pneumonia, diarrhea, and common cold has been reported. It is expected that the most pronounced effect of zinc supplementation may be observed in individuals with subclinical or severe zinc deficiency. Due to the high incidence of zinc deficiency, as well as its significant contribution to a wide range of pathologies, the correction of low zinc level may be considered as economically effective strategy. Thus, the results of the existing studies have demonstrated the efficiency of zinc intake for prophylaxis or as an adjuvant therapy of a wide range of pathologies.